Horizontally plasmon hybridization on symmetric-breaking metamaterials - Thi Hien, Nguyen; Son Tung, Bui; Xuan Khuyen, Bui; Van Dung, Nguyen; Thanh Viet, Do; YoungPak, Lee; Thanh Tung, Nguyen; Dinh Lam, Vu (Vietnam Journal of Science and Technology, 2017)
In this report, we present a study on the fundamental negative-permeability metamaterials, named as the cut-wire-pair structure. The physics of the cut-wire-pair metamaterial is interpreted using the electromagnetic analog of molecular-orbital theory. It is shown that a symmetric-breaking cut-wire-pair metamaterial is horizontally plasmon-hybridized, leading to an additional magnetic resonance beyond the conventional one. The transmission spectra and the induced energy distributions are performed to demonstrate our prediction.